Methodology for compiling a clinical situation task and a checklist for a professionally based exam - E. Yu. Vasilieva; N. V. Skripova; N. G. Davydova (LLC "Endo Press", 2019)
The relevance of the study is due to the need to develop a measuring tool for assessing the professional competencies of future dentists in quasi-professional activities (at the examination in the discipline «Stomatology»), which meets the requirements of vigilance and reliability. The purpose of the study was to substantiate the methodology for compiling a clinical situational task and check-lists for a professionally oriented exam. The material and methods are presented on the basis of the formed experience of compilation and approbation of clinical situational tasks and attached check-lists during the professional-oriented examination in the discipline «Dentistry» for three years at the Northern State Medical University. The results of the research reveal the process of developing a clinical situational task using the example of a task designed to assess the professional competencies of the examiners based on the results of studying the «Endodontics» module.